Managerial Ownership, the Method of Payment for Acquisitions, and Executive Job Retention - Ghosh, Aloke; Ruland, William (Journal of Finance, 1998)
ABSTRACT This study investigates how acquiring and target firm managers' preferences for control rights motivate the payment for corporate acquisitions. We expect that managers of target firms who value influence in combined firms will prefer to receive stock. One reason top managers desire influence is to enhance their chances of retaining jobs in the combined firm. Our analysis shows a strong, positive association between managerial ownership of target firms and the likelihood of acquisitions for stock. We also find that managers of target firms are more likely to retain jobs in combined firms when they receive stock rather than cash.